From Home to Self: Investigating the Correlation Between Family Harmony and Self-Acceptance - Istiana, Istiana (Bulletin of Counseling and Psychotherapy, 2025)
A harmonious family dynamic provides students with the support and stability needed to develop a positive self-concept, which is crucial for their personal and academic growth. This research aims to provide an overview and determine the relationship between family harmony and self-acceptance of students at Universitas Medan Area. The research was carried out using a quantitative method with a correlational design, which aims to identify the relationship between two or more variables without manipulating them. The data for this study were obtained from students enrolled at several universities across North Sumatera, specifically Universitas Medan Area (UMA) with 252 participants, Universitas Muhammadiyah Sumatera Utara (UMSU) with 140 participants, and Universitas Pembangunan Panca Budi (UNPAB) with 78 participants, resulting in a total sample of 470 students. The sampling technique employed in this research was purposive sampling. The data analysis technique uses Pearson Product Moment Correlation. The results indicate a strong or significant influence between Family Harmony on Students’ Self-Acceptance in Universitas Medan Area. This is known through analysis and processing of questionnaire data which results in a correlation coefficient of 0.497, this means that there is a positive relationship between self-acceptance and family harmony.